Love potion - Launer, Dale; Launer, Dale; Launer, Dale (Twentieth Century Fox Home Entertainment, 1992)
In this charming romantic comedy, a brilliant but lonely biochemist gets a nysterious potion from a gypsy who guarantees it will turn his life around. After showing it to his co-worker, a shy animal psychobiologist, they achieve amazing amorous results in a chimpanzee experiment. Now the only way to see if it works on humans is to test it on themselves.